Challenges faced by people with a stoma: peristomal body profile risk factors and leakage. (7th April 2022) - Martins, Lina; Andersen, Birgitte Dissing; Colwell, Janice; Down, Gillian; Forest-Lalande, Louise; Novakova, Svatava; Probert, Rosalind; Hedegaard, Chris Juul; Hansen, Anne Steen
Abstract : Aim: The Ostomy Life Study 2019 aimed to obtain a better understanding of the challenges faced by people with stoma. Methods: Online survey with participants from 17 countries. Findings: Of the 54 614 individuals invited to take part, 5187 responded; 62% of the respondents avoided physical and social activities because of their stoma and 37% had never consulted their stoma care nurse to have the fit of their stoma product checked. In a subgroup receiving questions on leakage ( n =4209), output under the baseplate and leakage onto clothes were experienced within the previous month by 76% and 26% of respondents, respectively. Higher chance of leakage was associated with an irregular stoma shape and peristomal body profile; a stoma level at or below the skin surface; and the presence of creases, folds and other changes in the peristomal area. Conclusion: Leakage and access to a stoma care nurse to provide the necessary care and guidance remain important concerns for individuals with a stoma.